A methodology for the evaluation of road accidents health care costs for powered two-wheelers: The Rome case study. Issue 2 (June 2017) - Corazza, Maria Vittoria; Musso, Antonio; Finikopoulos, Kostas; Sgarra, Veronica
Highlights: Health care costs for road safety victims are calculated according to different approaches. A case study on these costs for PTWs victims in Rome is proposed. The calculation approach is based on the Italian regulatory reference. The calculation of the Safety Potential index integrates this approach. Abstract: Road safety is a central issue in many political agendas virtually worldwide, scientific literature on road accidents prevention abounds as the consequent awareness of the higher vulnerability of Powered Two-Wheelers (PTWs). Not the same can be said about the assessment of the economic side of the problem: decision-makers seem to underestimate the relevance of public health care costs to recover and rehabilitate those involved in road accidents, especially riders. The paper, thus, deals with a specific approach to assess the current methods to estimate health care costs due to road accidents, with the goal to have a special focus on the problems arising when the PTWs are involved. The motivation for such approach is due to the unsuitability of these current methods, which underestimate the health care costs. Therefore, the paper reviews some references for health care costs, which often are parts of the calculation of the overall road safety social costs. Although the effectiveness of these methods is undisputable, more specific criteria and indicators are required to have health care costs properly assessed, especially about PTWs, since no univocal cost items are considered; consequently health care expenditures markedly vary. The paper, then, analyzes the road accidents occurred in Rome, Italy, from 2010 to 2012, as a case in point of this problem, defines the health care costs occurred and revises results taking as leading criteria the level of vulnerability of the involved PTWs victims and the severity of the event, in order to provide more accurate estimations of such costs.